MENINGKATKAN KETERAMPILAN MENULIS TEKS EKSPOSISI MELALUI MODEL PEMBELAJARAN INVESTIGASI KELOMPOK DENGAN MEDIA ZOOM MEETING DAN GOOGLECLASSROOM SISWA SMPN 11 JAKARTA - MASRUROH MASRUROH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
This study aims to improve students' skills in learning to write exposition texts and motivate students to get satisfactory knowledge scores. This class action research was carried out in two cycles, carried out from the month of Agustus until October 2021 in class VIII D of SMPN 11 Jakarta. Most students have not understood the material of the Exposition text. The factors that affect it include (1) lack of interest in learning Indonesian (2) Lack of communication in the learning process (3) Lack of supporting prerequisites in students. The foregoing is the result of observations that the researchers obtained from the list of Indonesian values that the researchers obtained in the material for writing class VIII D exposition texts in the 2021/2022 academic year. From this background, researchers have a problem